How to Measure Emotional Intelligence in Early Adolescence Age - Babić Čikeš, Ana; Buško, Vesna (2010)
There are a growing number of emotional intelligence researches in the past twenty years, but very few of them studied emotional intelligence in early adolescence age. Among the reasons is, that we lack well developed emotional intelligence tests designed for this age and measurement problems in research of emotional intelligence are still unresolved. This study aims to present preliminary findings pertaining to the development and validation of a new performance instrument intended to measure emotional management ability (following the Mayer and Salovey model). The instrument is designed especially for the early adolescence age. Participants of the study were students of higher grades of an elementary school in Croatia. We administered the new test (Emotional Management Ability Test) along with two additional performance tests of emotional intelligence abilities: Perception of Affective Content in Art designed to assess perception of emotions, and Emotional Analysis Test intended to measure understanding and analysis of emotions. Data on school achievement and the self-report data based on an instrument for the assessment of empathy were also collected. Low, but significant correlations were found between the Emotional Management Test and the two other measures of emotional intelligence, Empathy questionnaire and school achievement, as well. Results are discussed in view of construct- and criterion-related validation of the operationalizations based on the Mayer and Salovey model.
Projekt MZOS
ENG